Cognitive Literary Studies: A Conversation with Marco Caracciolo, Monika Fludernik, Patrick Colm Hogan and Karin Kukkonen (ENTHYMEMA, 2022)
The article proposes a conversation on Cognitive Literary Studies with Marco Caracciolo, Monika Fludernik, Patrick Colm Hogan and Karin Kukkonen. Starting from a methodological reflection on the interdisciplinarity of this field, the scholars were asked to consider its foundations by focusing on the relationship between science and literature, and lastly to ponder the prospects of narrative theory, cognitive narratology and literary universals. The interview is preceded by a brief introduction which attempts to outline its purpose.
Keywords: Cognitive Science; Literary Theory; Narratology; Literary Universals; 4E Cognition